Development of Microwave Split Ring Resonator (MSRR) for solid material characterization - Meor Said, Maizatul Alice; Zakaria, Zahriladha; Misran, Mohamad Harris (Penerbit UTeM Press, 2025)
Development of Microwave Split Ring Resonator (MSRR) for Solid Material Characterization discover the inductive energy transfer and material characterization with this easy-to-understand guide. This book explores the innovative technology of split ring resonators (SRR) and learn about microwave resonator sensors and how they are used. Starting with the fundamental principles of split ring resonators and microwave sensors, the book addresses the challenges and goals of this cutting-edge research. It offers a detailed exploration of microwave resonator sensor design, comparative material characterization methods, and the critical perturbation technique. With clear explanations of mathematical analysis, formula, simulations design, fabrication, and testing, readers will learn how to design high-sensitivity planar microwave sensors. Diagrams and flow charts make the learning process easier and more engaging, helping to understand complex ideas. Ideal for researchers, engineers, and students, this book equips readers with the tools and knowledge to revolutionize communication links and material characterization techniques. Dive into the future of sensor technology and energy transfer with this essential resource.